The Urban Space of Network Society: Digital Flaneurs in the Age of Social Media - Iavarone, Ayşenur Hilal; Dursun Çebi, Pelin (My University, 2019)
This paper stems from the idea that individuals in the network society have a new type of spatial perception and experience in the urban context. In this context, the study distinguishes itself from the discussions, such as virtual space and digitalization on architecture, which is frequently included in today’s debates, and refers to changing urban space experiences and the practices of network society. In the age of mobile devices and social media, the social structure of society, forms of communication and experience of being in the urban space have been changed. This transformation also creates its own perception and experience of urban space as well as it creates new everyday- life practices. This study exanimates specific kinds of urban experiences and practices that can be formed by social media usage in the urban place to understand the meaning of architectural space for the network society. This essay addresses the following questions: How location based social media practices create a digital version of flaneur in the digital age in sense of urban discovery? How network society creates social media-based practices in everyday-life? These questions will be answered throughout this study, by focussing on the concepts and spatial practices of network society, everyday- life and flaneur in the digital age. To exemplify transformation of bodily experience in urban space, the concept of "digital flaneur1’ (Skees, 2010) has been utilized for the spatial inquiry. Location-based social media causes transformation of urban space by creating new experiences on physical space. Just as the flaneur (Benjamin, 1983) drifted though the city without a path, location-based social media users explore the city through media without physical paths. As a concept, "digital flaneur” reconsiders the body in the network society, as Benjamin describes, an idle that strolls in the city to investigate the urban life in it (Benjamin, 1983). Digital flaneur term is used for the stroller body that explores digital space and engages physical space at the same time through location-based social media. With these digital experiences in virtual space, this new body develops an individual attitude on urban space.In order to find answers to the above research questions, digital flaneur’s location-based social media practices will be analysed. Memory collecting, sharing, rewriting and rereading practices will be collected from selected social media platforms and illustrated in order to understand digital version of being in urban space. Within the scope of the study, urban space of the network society is expected to resolved and discussed through analysis of location-based social media practices.
Keywords: Network Society; Location Based Social Media; Urban Space; Digital Flaneur; Eveyday-Life Practices; Ağ Topluluğu; Lokasyon Bazlı Sosyal Medya; Kentsel Mekan